Triple-functional fluoropolymers for inkjet-printing perovskite light-emitting diodes. (December 2022) - Xie, J.; Liu, L.; Piao, J.; Ge, H.; Wang, Y.; Yang, H.; Shen, W.; Cao, K.; Chen, S.
Abstract: Metal halide perovskite materials are regarded as one of the most promising semiconductors for achieving high-performance light-emitting diode (LED) displays. Inkjet printing is an emerging technology for next-generation display, due to its unique advantages of high material utilization, large scalability, mask-free and high-resolution patterning. However, it is still a challenge to realize precise control of perovskite crystalline dynamics in inkjet printing process. Here, triple-functional fluoropolymers are introduced into perovskite precursor inks. First, the fluoropolymers play a key role in tuning the perovskite crystal-growth, which is ascribed to the –CF2 -/FA + interaction and polymer chain entanglement, leading to a decreased crystal size, a uniform and smooth film morphology. Then, the –CF2 -/Pb + and –CH2 -/Br − interactions provide a passivating effect, contributing to an enhanced photoluminescence intensity and prolonged charge carrier lifetime. Furthermore, the hydrophobicity of fluoropolymers is beneficial to improve the humidity stability of perovskite films. Finally, on behalf of the superiorities of fluoropolymers, complex perovskite patterns are successfully printed and applied in information encryption as well as perovskite LEDs, which achieve a maximum luminance of 12738 cd/m 2 and a current efficiency of 15.5 cd/A. This work demonstrates the benefits of triple-functional fluoropolymers in inkjet-printing perovskite films with controllable crystalline process for information encryption and display applications. Graphical abstract: Image 1 Highlights: Fluoropolymers of PVDF and PVDF-HFP are introduced into perovskite precursor inks for inkjet printing. The fluoropolymers can tune perovskite crystal growth by providing nucleation sites and chain entanglement. The interactions between fluoropolymer and perovskite provide a passivating effect. The hydrophobicity of fluoropolymers is beneficial to improve the humidity stability of perovskite films. Complex perovskite patterns are successfully printed and applied in light-emitting diodes.